Hematology and biochemistry reference intervals for American crocodiles (Crocodylus acutus) in South Florida - Balaguera-Reina, Sergio A.; Jennings, Nicole D.; Godfrey, Sidney T.; Brandt, Laura A.; Daykin, Bryna; Squires, Michiko A.; Mazzotti, Frank J. (Frontiers in Veterinary Science, 2022)
The American crocodile (Crocodylus acutus) is considered a vulnerable species by the IUCN Red List across its range and classified as locally threatened in several countries. There is a lack of knowledge involving hematological and physiological parameters in American crocodile populations, limiting our understanding of what are considered “normal” blood analyte results for the species, and how to link them with health assessments. In this study, we analyzed 40 hematological and biochemistry parameters and estimated reference intervals (RIs) for 35 of them based on 436 clinically healthy wild American crocodiles caught in South Florida between 2015 and 2021. Crocodiles were captured across three areas with different levels of human influence [low = Everglades National Park (ENP), medium = Biscayne Bay Estuary (BBE), and high = Turkey Point Nuclear Power Plant (TP)]. There was very strong-to-strong evidence for an effect of where animals were caught on five analytes: basophils %, phosphorus, proportion of (pr) alpha 2 globulins, absolute count (abs) of gamma globulins, and corticosterone, so no reference values were estimated but general statistics are presented and discussed. From the remaining analytes, we found no evidence that sex or size class had an effect on red blood cell (RBC), azurophils and monocytes abs, triglycerides, and albumin abs. However, we did find moderate-to-strong evidence that sex influenced azurophils %, and size class influenced white blood cell (WBC), heterophils %, monocytes %, basophils abs, creatine phosphokinase (CPK), potassium, glucose, bile acids, alpha 1 globulin abs, and alpha 2 globulin pr and abs. Finally, there was strong evidence that both sex and size class influenced PCV, lymphocytes % and abs, eosinophils % and abs, aspartate aminotransferase (AST), calcium, sodium, chloride, total protein, albumin/globulin (A/G) ratio, albumin pr, alpha 1 globulin, and beta globulin abs. Intraspecific analysis showed that size is the variable that most influenced analytes explaining up to 29 % of the variation, which relates with our findings based on intraindividual analysis. We compared our results with blood parameters reported for conspecifics as well as closely related species and discussed implication of those results for clinical diagnosis and American crocodile conservation.